The Advent project : the later-seventh-century creation of the Roman Mass proper - McKinnon, James W., 1932-1999 (University of California Press, 2000)
In his final accomplishment of an extraordinarily distinguished career, James W. McKinnon considers the musical practices of the early Church in this incisive examination of the history of Christian chant from the years AD 200 to 800.